Interspecies Interactions Between Streptococcus Mutans and Streptococcus Agalactiae in vitro - Liu, Tingjun; Liu, Jia; Liu, Jianwei; Yang, Ruiqi; Lu, Xianjun; He, Xuesong; Shi, Wenyuan; Guo, Lihong (Frontiers in Cellular and Infection Microbiology, 2020)
More than 700 species of bacteria are inhabited in the oral cavity. Streptococcus mutans (S. mutans) is an early oral colonizer and major etiological bacteria involved in early childhood caries (ECC). Interspecies coaggregation plays a crucial role in facilitating close intercellular communication and polymicrobial pathogenesis. We aimed to find undiscovered binding partners of S. mutans and to investigate interactions between them. S. mutans physically bonded with original saliva isolate Streptococcus agalactiae (S. agalactiae, also known as Group B Streptococcus, GBS)-SI101 in vitro. In contrast to gtfD-deficient strain and the parent strain of S. mutans, gtfB-, gtfC-, gtfBC-, and gtfBCD-deficient strains of S. mutans displayed significantly reduced levels of interspecies binding with GBS-SI101. Loss of luxS in S. mutans barely affected GBS-SI101 integration into S. mutans biofilm. In addition, oral Streptococcus species were tested for growth competition with GBS-SI101, including S. mutans, Streptococcus sanguinis (S. sanguinis), and Streptococcus gordonii (S. gordonii). Results revealed none of these Streptococcus species or their metabolites inhibited the growth of GBS-SI101. Our study firstly identified physical interplay between S. mutans and original saliva isolate GBS-SI101. GtfB and GtfC of S. mutans, which were mainly responsible for insoluble glucans synthesis, played important roles in the dual-species coaggregation between S. mutans and GBS-SI101. Moreover, GBS-SI101 encountered little growth antagonism from common oral Streptococcus species tested in our study, indicating that GBS might successfully integrate into oral streptococci-associated oral biofilms instead of simply passing through the oral cavity.